2011
DOI: 10.2478/s11756-011-0089-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of natural enemies on Obolodiplosis robiniae invasion

Abstract: Abstract:The gall midge Obolodiplosis robiniae is a pest of black locust Robinia pseudoacacia. The species was recently introduced into Europe and it is nowadays a usual insect in Slovakia, where two-year field surveys were undertaken during [2007][2008]. The main objective of this study was to determine the natural enemies attacking O. robiniae and estimate their influence on midge population, less than 3 years after its introduction. Eight parasitoids and bushcricket Tettigonia viridissima were responsible f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Often, several females have laid eggs in the same place, and the larvae develop a standard gall where they feed (Molnár et al, 2009). As a result, the average number of larvae in a gala is up to 5-6 larvae (Skuhravá et al, 2007;Tóth et al, 2011), and the maximum number can reach 9-11 larvae (Pernek and Matošević, 2009;Mocreac and Timuş, 2014;Csóka et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Often, several females have laid eggs in the same place, and the larvae develop a standard gall where they feed (Molnár et al, 2009). As a result, the average number of larvae in a gala is up to 5-6 larvae (Skuhravá et al, 2007;Tóth et al, 2011), and the maximum number can reach 9-11 larvae (Pernek and Matošević, 2009;Mocreac and Timuş, 2014;Csóka et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The assessment and forecasting of the impact of invasive alien species on a global scale have drawn a lot of research interest [ 35 , 36 ]. O. robiniae , a native of the Nearctic region, invaded almost simultaneously from the eastern and western parts of Eurasia at the beginning of the 21st century, and it then spread rapidly, thanks in large part to the belief that it did not pose a serious threat to forest stands, frequent trade activities, and the widespread presence of its host R. pseudoacacia [ 11 , 37 ]. However, our investigation revealed that human negligence was the primary cause for its spread in almost every region inhabited by R. pseudoacacia in China.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the natural enemies of O. robiniae include predatory insects such as lacewings, ladybeetles, and crickets [ 37 , 53 ], as well as parasitic insects such as Platygaster robiniae Buhl and Duso, Eupelmus urozonus Dalman, and Mesopolobus mediterraneus Mayr, [ 37 , 54 ], with P. robiniae occupying a dominant position in parasitic wasps. It has been detected in European and East Asian countries, where it is considered to be one of the key contributors lowering the O. robiniae population density [ 55 , 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…R. pseudoacacia affects numerous ecosystem components leading to the modification of plant and lichen communities, decreasing the richness and diversity of soil invertebrate fauna [19][20][21], to the detriment of birds too [22]. Natural enemies may significantly influence the spread of non-native animals and plants, changing the strength of interactions between these species and the native community -e.g., by decreasing the density and competition of non-native/alien species [23][24][25]. In its native area of North America, more than 70 insect species prey on R. pseudoacacia and some of them were introduced to Europe incidentally [26,27].…”
Section: Introductionmentioning
confidence: 99%